BENEFITS OF ACTIVE INFERENCE METHOD FOR TRAINING PROCESS ANALYSIS IN ELITE ALPINE SKIING SPORT - Shestakov, M.P.; Kryuchkov, A.S.; Shevtsova, I.G.; Navolotsky, A.A.; Fomichenko, T.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to theoretically analyze and test benefits of an active inference method for training process in elite alpine skiing sport. Methods and structure of the study. We sampled for the active inference method testing experiment national alpine skiers (n=20, equal gender split), qualifiers for the World Cup and tested their training progress by a) Stabilan-01 stabilometric test system with a biological feedback capacity, b) dopamine levels. Results and conclusion. Dopamine levels in blood served as an indicator of changes in the athletes’ movement control system; these changes were related to execution of different training loads. We registered a decrease in prediction errors after the 21-day long training period aimed at technique adjustment, if compared to the other 21-day long training period aimed at improvement of physical capacities. As provided by the modern theory of active inference, these progresses are largely due to improvements in the somatosensory prediction of the movement results system performance and, as a result, progress forecasts depending on the somatomotor system state.